Older adults’ perspectives on HIV/AIDS prevention strategies for rural Kenya - Muturi, Nancy W.; Mwangi, Samuel (My University, 2012)
Though prevention of HIV/AIDS is the mainstay of various responses to the epidemic,communication strategies used to motivate behavior change are challenged for lack of cultural appropriateness, hence the lack of success. Participatory communication that is culture-centered and culturally sensitive is emphasized in HIV/AIDS communication to engage affected communities in defining problems and finding appropriate solutions. This paper examines the views of older adults as key targets in HIV/AIDS prevention given the increasing number of elderly living with the disease and their changing role as caregivers of those infected and affected by HIV. As cultural, social, political, and opinion leaders in rural communities, older adults are in a position to influence attitudes and behaviors of their community members, but they have not been involved in the current HIV/AIDS prevention interventions. Several recommendations were made to inform the design and implementation of a culture-specific prevention program for rural Kenya.
Keywords: HIV/AIDS; Kenya; Rural; Older adults